‘People have Started Calling Me an Expert’: The Impact of Open University Microcredential Courses - Chandler, Kathy; Perryman, Leigh-Anne (Journal of Interactive Media in Education, 2023)
Evaluating courses' impact on diverse stakeholders can be immensely valuable as a means of identifying ways in which curriculum can better support learners' personal and professional development and achieve wider societal aims. Yet, few empirical evaluation studies exist exploring the impact of microcredentials. This article reports a study intended to address that knowledge gap by examining the impact of microcredential courses provided by The Open University UK - one of the largest universities in Europe. A survey and narrative interviews were used to explore courses' impact on learners' knowledge, attitudes, behaviours and practices six months after the course ended. Analysis of the data, and the application of Wenger, Trayner and de Laat's (2011) Value Creation Framework, suggests that microcredential courses do have impact, in multiple ways, even for those learners not completing their course. Areas of impact include the development of learners' knowledge and skills, changed thinking about the subject studied, and impact at work and/or on everyday life. For some learners, study of a microcredential course also enables a career change or provides the confidence to go on to further study. Keywords: microcredential, impact, evaluation, narrative